Starch structure and some properties of cocoyam (Xanthosoma sagittifolium and Colocasia esculenta) starch and raphides - Sefa-Dedeh, S.; Kofi-Agyir Sackey, E. (Food Chemistry, 2002)
Studies were conducted on the structure and rheological properties of three cocoyam varieties [Xanthosoma sagittifolium (red-flesh), Xanthosonia sagittifolium (white-flesh) and colocasia esculenta] starches and raphides in an attempt to characterize them. The microstructures of starch granules and raphide sizes, which were obtained from the distal, middle and apical sections of the raw cocoyam samples, were examined using a light microscope. Evaluations of the rheological properties of the cocoyam species were also conducted, using a Brabender viscoamylograph. No distinct variation was observed in starch granule sizes of the two Xanthosoma species. Starch granules sizes in the ranges of 0.74-1.19 and 0.74-1.10 μm were obtained for the Xanthosoma species (red-flesh) and Xanthosoma species (white-flesh), respectively. Significantly smaller sizes (0.05-0.08 μm) of starch granules were observed for Colocasia esculenta. Microstructures of raphide sizes which were obtained from the distal section of the cocoyam species showed significant differences (P≤0.05) among the varieties, with the Colocasia species having more pronounced needle-like structures. Evaluation of the rheological properties of the cocoyam flours, using the Brabender viscoamylograph, showed considerable variations among the varieties, especially between the Xanthosoma species and the Colocasia species. The C. esculenta showed lower hot paste viscosity but higher thermal stability than the Xanthosoma species. Peak viscosity was highest in the X. sagittifolium (red-flesh) variety while the white-flesh variety showed the least tendency to retrogradation. © 2002 Published by Elsevier Science Ltd.
Keywords: Colocasia esculenta; Rheological properties; Starch and raphides; Starch structure; Xanthosoma sagittifolium